2020
DOI: 10.1302/2046-3758.99.bjr-2020-0135.r1
|View full text |Cite
|
Sign up to set email alerts
|

A higher degree of polyethylene irradiation is associated with a reduced risk of revision for aseptic loosening in total hip arthroplasties using cemented acetabular components

Abstract: Aims To investigate the effect of polyethylene manufacturing characteristics and irradiation dose on the survival of cemented and reverse hybrid total hip arthroplasties (THAs). Methods In this registry study, data from the National Joint Registry of England, Wales, Northern Ireland and the Isle of Man (NJR) were linked with manufacturing data supplied by manufacturers. The primary endpoint was revision of any component. Cox proportional hazard regression was a primary analytic approach adjusting for competing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
(30 reference statements)
1
6
0
Order By: Relevance
“…Second, as mentioned earlier, the mechanism of initially unstable implants as presented here might not reflect the mechanism of long-term loosening due to wear, but this problem seems to be diminished with the use of contemporary polyethylenes, 39 and modern 3D-printed implant coatings and designs might reduce the risk of initially unstable implants. 40 Translationally, our data suggest that iPTH can directly influence osseointegration at the bone-implant interface for patients with an initially unstable implant.…”
Section: Discussionmentioning
confidence: 77%
“…Second, as mentioned earlier, the mechanism of initially unstable implants as presented here might not reflect the mechanism of long-term loosening due to wear, but this problem seems to be diminished with the use of contemporary polyethylenes, 39 and modern 3D-printed implant coatings and designs might reduce the risk of initially unstable implants. 40 Translationally, our data suggest that iPTH can directly influence osseointegration at the bone-implant interface for patients with an initially unstable implant.…”
Section: Discussionmentioning
confidence: 77%
“…The revision CTHR procedure may be a convoluted and backbreaking procedure, predominantly in younger and more active patients who urgently need limb function recovery from injury [ 8 , 20 ]. Nevertheless, revision CTHR may exacerbate the occurrence of component loosening as a result of the well-established inequality between axial and rotating loads caused by massive bone loss [ 7 , 34 ]. Component loosening attributed to the combination of implant type and osteolysis (or infection) could lead to the revision of secondary CTHRs [ 20 , 34 ], although distinctions between primary and secondary CTHRs are still being debated [ 18 , 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the expansion of surgical indications for total hip replacements (THRs) [ 4 ], it is expected to increase the demand for THRs, which are a universal and reliable procedure characteristically executed for the reduction of hip symptoms and have been approved as a surgical protocol for converting a failed fixation of PFFs with the aim of relieving pain, strengthening stability, and restoring function [ 5 , 6 ]. Despite improved hip function attributed to THRs, prior studies [ 7 , 8 ] have indicated that approximately 15% of patients have to deal with this dilemma of component loosening that may have unfavorable kinematic aftereffects since mechanically aligned components may be passively shifted and trigger a variation in the angle of the femur, which can eventually lead to premature failure of THRs. Furthermore, available data [ 9 , 10 ] indicate that component loosening is commonly regarded as a catastrophic failure of THRs owing, to some extent, to concern over reduced component survival.…”
Section: Introductionmentioning
confidence: 99%
“…21 To further eliminate confounding factors and focus on current bearing choices, we restricted the sample to polyethylene liners irradiated with 5MRad or more, classified as highly crosslinked (XLPE), in keeping with our previous work and other registries. 2 , 22 , 23 Our methodology has been described in detail in our previous study on polyethylene modifications. 2 …”
Section: Methodsmentioning
confidence: 99%